Concept for Common European TV Channel - Slavinski, A.; Draganov I. (European Journal of Multidisciplinary Studies, 2018)
One of the problems, which lies ahead of the EU and the European Integration is how can people from different nationalities learn more about each other. In this problem, there is a severe lacking of progress. Thus, in light of European’s people natural desire of better understanding and successful collaboration in the advancement of common European values, comes the need of a Pan-European TV channel. ?V PanEurope+ will help in an effective way for the common understanding of the history, the culture, the tourism, the customs of the European people.